Online Child Sexual Exploitation in the Philippines: Moving beyond the current discourse and approach - Gill, Melinda (Anti-Trafficking Review, 2021)
Online child sexual exploitation (OCSE) is an issue of increasing concern in the Philippines. The current local discourse concerning OCSE is that it primarily involves children being sexually exploited by adults within their household or in ‘dens’, with ‘raid and rescue’ operations and public awareness campaigns as the most publicised strategies employed to address the issue. Whilst the true prevalence of OCSE is unknown, ongoing research and the experience of many stakeholders suggest that self-generated sexual content involving children is common. However, this is not being widely discussed or addressed. This article argues that more holistic, long-term, and community-based interventions targeted at vulnerable families and children are needed that address the deeper determinants of OCSE in the Philippines.